Influence of citrate-stabilized Cu- and Mn-nanocolloids on the growth and proliferative activity of Allium cepa L. apical meristems - Konotop, Ye.O.; Karpets, L.-A.; Zinchenko, A.V.; Lopatko, S.K.; Kovalenko, M.S.; Smirnov, O.E. (Reports of the National Academy of Sciences of Ukraine, 2019)
Using the standard Allium-test system, the phytotoxicities of Cu- and Mn-containing nanocolloids obtained in the absence and presence of a stabilizer are compared. The toxicities of the studied solutions are assessed by growth indicators of Allium cepa L. roots, and their cytotoxicity by the proliferative activity of the root meristem cells. Solutions of stabilized nanocolloids are more toxic for A. cepa L. plants in terms of the integral index of root growth, but are not cytotoxic. The differences in the phytotoxicities of stabilized and unstabilized nanoparticles depend on their properties and consist in influencing the various mechanisms of onion root growth such as mitosis and “acid” growth.